Improving the Measurement of Rural Women's Employment : Global Momentum and Survey Research Priorities - Koolwal, Gayatri B. (World Bank, Washington, DC, 2019)
Rural economies are in transition around the world; in many countries, improved technology and linkages across sectors have expanded access to markets and accelerated production for some farmers. At the same time, rural areas globally are facing a growing base of landless and smallholder farmers, out-migration to urban areas, and persistence of low-skilled, informal, and seasonal jobs where women are often heavily concentrated. Recent global initiatives are examining programs that can effectively raise rural incomes, including how addressing shortfalls in wome's hours worked and earnings can raise rural productivity and growth. But well-designed policies to address these issues require improved counting of individuals' employment, accounting for the complexity of measuring rural women's labor force participation, as well as data on social, economic, and institutional constraints that women face in seeking better economic opportunities. Using recent rounds of the Ethiopia, Malawi, Nigeria, and Uganda Living Standards and Measurement Study-Integrated Surveys on Agriculture, as well as findings from recent country pilots conducted by the International Labour Organization, this paper discusses best practices and issues to consider when examining rural women's employment in socioeconomic surveys, as well as a survey research agenda to improve measurement.